PERAN FAKTOR EKONOMI MAKRO DALAM MEMODERASI PENGARUH TINGKAT KESEHATAN BANK TERHADAP PENILAIAN SAHAM (Studi Pada Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2024) - Revalina Dewita Sari; Mahatma Kufepaksi; Nindytia Puspitasari Dalimunthe (Nusantara Hasana Journal, 2026)
This study aims to analyze and test the effect of bank health level using a risk approach (Risk-Based Bank Rating) consisting of liquidity risk, credit risk, good corporate governance (GCG), earnings, and capital on stock valuation as measured by price to book value (PBV) with macroeconomic factors such as inflation and interest rates as moderating variables and bank size and company growth as control variables in the banking sector listed on the Indonesia Stock Exchange for the period 2015-2024. The population of this study consisted of 47 banking companies, with a purposive sampling technique obtained 38 companies as samples, while data analysis was carried out using Panel Data Regression and Moderated Regression Analysis (MRA) through Eviews 12 software. Interest rates negatively moderate or weaken the positive effect of capital adequacy on stock valuation, because investors consider that the capital owned by banks is vulnerable to pressure from macroeconomic factors. In this condition, investors will move funds to safer and more stable instruments, so that the valuation of banking stocks decreases. Therefore, in this study, interest rates negatively moderate (weaken) the positive influence of capital adequacy levels on stock valuations in the banking sector.